Palladium-Catalyzed, Enantioselective Formal Cycloaddition between Benzyltriflamides and Allenes: Straightforward Access to Enantioenriched Isoquinolines - Vidal, Xandro (J Am Chem Soc, 2019)
[Image: see text] Benzyl and allyltriflamides can engage in Pd-catalyzed oxidative (4+2) annulations with allenes, to produce highly valuable tetrahydroisoquinoline or dihydropyridine skeletons. The reaction is especially efficient when carried out in the presence of designed N-protected amino acids as metal ligands. More importantly, using this type of chiral ligands, it is possible to perform desymmetrizing, annulative C–H activations of prochiral diarylmethylphenyl amides, and thus obtain the corresponding isoquinolines with high enantiomeric ratios.